Hand function assessment in the first years of life in unilateral cerebral palsy: Correlation with neuroimaging and cortico-spinal reorganization. (January 2016) - Baranello, Giovanni; Rossi Sebastiano, Davide; Pagliano, Emanuela; Visani, Elisa; Ciano, Claudia; Fumarola, Adriana; Arnoldi, Maria Teresa; Corlatti, Alice; Foscan, Maria; Marchi, Alessia; Erbetta, Alessandra; Riva, Daria
Abstract: Aim: The purpose of the present study was to correlate early hand function assessment during the first years of life with neuroimaging findings and the different patterns of cortico-motor reorganization in children with unilateral cerebral palsy (UCP). Methods: We conducted a long prospective observational study, in which 17 children with UCP (8 left-sided hemiplegia; Manual Ability Classification System level 1–3) were first assessed at a mean age of 24 months (range 18–28), and followed up by means of the Besta Scale, a new standardized protocol assessing both unimanual and bimanual hand function. They also underwent Melbourne Assessment of Unilateral Upper Limb Function (MUUL) and single-pulse Transcranial Magnetic Stimulation (TMS) at a mean age of 10 years 5 months (range 9 y 1 m–12 y 8 m). Brain MRIs of all the 17 children were independently assessed and scored by two blinded observers, according to a defined protocol. Possible correlations between hand function at first assessment, neuroimaging and TMS data were analyzed. Results: Early hand function impairment significantly correlated with the extension of brain damage ( ρ  = −0.531, p  = 0.028), number of involved areas ( ρ  = −0.608, p  = 0.010), presence of radiological signs of cortico-spinal degeneration ( ρ  = −0.628, p  = 0.007), and basal ganglia involvement ( ρ  = −0.485, p  = 0.049). Additionally, higher hand function scores (i.e. better hand function) at first assessment significantly correlated with contralateral cortico-spinal projections, while lower scores significantly correlated with either mixed or ipsilateral cortico-spinal projections to the affected hand ( χ 2 (2) = 11.418, p  = 0.003; post-hoc tests: contralateral TMS group versus ipsilateral: Z = −2.943, p = 0.002 and contralateral TMS group versus mixed: Z = −2.775, p = 0.006). Conclusions: To our knowledge, this is the first study correlating hand function assessment in the first years of life, and its evolution over time, with neuroimaging and cortico-spinal projection patterns in children with UCP. These findings could contribute to an improved prediction of prognosis and a better delineation of therapeutic interventions in young children with UCP. Highlights: A new scale for hand function was applied in a sample of UCP children since the first years of life. Early hand function scores correlated with neuroimaging and cortico-spinal (CS) reorganization. Hand function scores significantly changed over time in the group as a whole, irrespective of CS projection patterns.